Feasibility, acceptability and appropriateness of laparoscopic versus abdominal hysterectomy for women and healthcare professionals: the LAVA trial qualitative process evaluation - Lynsay Matthews; T Justin Clark; Sheriden Bevan; Lee Middleton; Lina Antoun; Paul Smith; Ertan Saridogan; Rebecca Woolley; Monique Morgan; Laura L Jones (Health Technology Assessment)
Background Laparoscopic hysterectomies performed for benign gynaecological conditions are increasing. However, there is a lack of up-to-date evidence on their surgical outcomes when compared with abdominal hysterectomy. The LAparoscopic Versus Abdominal hysterectomy trial aimed to address this gap. A qualitative process evaluation was embedded within the pilot phase of the LAparoscopic Versus Abdominal hysterectomy trial. Objective To explore the feasibility, acceptability and appropriateness of LAparoscopic Versus Abdominal hysterectomy for women and healthcare professionals. Design and methods A qualitative process evaluation using semistructured interviews informed by the Medical Research Council/National Institute for Health and Care Research updated Framework for Developing and Evaluating Complex Interventions. Interviews were thematically analysed to inform the development of a LAparoscopic Versus Abdominal hysterectomy trial programme theory (used to demonstrate how an intervention is expected to lead to its effects, under what conditions and for which stakeholders). Setting and participants Eligible women and healthcare professionals (gynaecologists, research nurses and research midwives) from participating clinical sites in National Health Service England. Main outcome measures Insight on the feasibility,acceptability and appropriateness of LAparoscopic Versus Abdominal hysterectomy related to the: (1) environment, (2) patient and (3) the healthcare professionals. Results Eleven women and 7 healthcare professionals (6 research nurses and 1 consultant gynaecologist) were interviewed. Four themes were interpreted. Theme 1 identified decision-making processes for LAparoscopic Versus Abdominal hysterectomy participation. Conditional altruism motivated women to participate, alongside the ‘relief’ of being offered a hysterectomy. The decision to decline participation was influenced by surgical preference and beliefs of laparoscopy having a faster recovery rate. Theme 2 highlighted surgical preferences, with women’s preferences being influenced by their previous experiences of surgery or perceived recovery times and family/friends. All healthcare professionals demonstrated community equipoise but did observe that ‘younger surgeons’ may prefer laparoscopic surgery based on their contemporary training. Theme 3 identified attitudes towards the LAparoscopic Versus Abdominal hysterectomy trial, with women and healthcare professionals reporting positively about LAparoscopic Versus Abdominal hysterectomy’s feasibility, acceptability and appropriateness in terms of burden, information and understanding of the study. Theme 4 identified the facilitators and barriers for LAparoscopic Versus Abdominal hysterectomy participation. Facilitators included the key role of the research nurses and women having personal social support during their recovery. Telephone consultations may be a barrier, with face-to-face discussion being preferred by both women and healthcare professionals. These findings informed the refinement of the LAparoscopic Versus Abdominal hysterectomy programme theory, identifying the interplay of factors related to the environment, patient and healthcare professionals. Limitations The majority of insight from women was gathered from one site (72.7%), and the majority of healthcare professionals’ insight was obtained from research nurses (85.7%). Only English-speaking participants were recruited into LAparoscopic Versus Abdominal hysterectomy. Conclusions Overall, LAparoscopic Versus Abdominal hysterectomy was acceptable for women and healthcare professionals. The trial, however, closed early due to the negative impact of the COVID-19 pandemic and lack of healthcare professional equipoise (these findings were published previously). The qualitative process evaluation highlighted additional factors to consider for future trials, including influences on women’s decision-making and the challenges of addressing patient and healthcare professional equipoise. Future work Comparison of laparoscopic and abdominal hysterectomy outcomes still need to be explored in a large-scale randomised controlled trial. Further qualitative insight is needed from women who decline participation and from healthcare professionals who lack equipoise. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR128991. Plain language summary A hysterectomy (surgery to remove the womb) can be performed in different ways. One way is by opening the abdomen, and one is by keyhole surgery, known as laparoscopy. There is not enough information yet to tell us how one surgery compares to the other. For example, the time it takes to recover or what the frequency of complications may be. The LAparoscopic Versus Abdominal hysterectomy trial aimed to answer these questions. However, trials like this can be difficult because women need to be willing to have either type of surgery. During the trial, we interviewed patients and health professionals to find out what they thought about the trial. Women said that they wanted to take part to help women in the future even if they potentially preferred one type of surgery. They were relieved to be offered a hysterectomy and did not mind which one they got. When women declined to take part, it was usually because they had a strong preference for one type of surgery. Although health professionals said they did not have a preference, they did suggest that ‘younger surgeons’ may prefer keyhole surgery due to taking part in recent training programmes. We only spoke with seven health professionals (one gynaecologist and seven research nurses), so an overall consensus is still uncertain. Unfortunately, the trial closed early. It was impacted by the COVID-19 pandemic and some health professionals, who chose not to take part in the study, had a preference for one type of surgery. This means that a future trial is still needed to help us compare the two different types of hysterectomy. We also need to understand why some women and health professionals did not want to take part in this trial. This will benefit the care of women in the future.